Erasmus+ and Educational Inspection in the Community of Madrid: Design, Development, and Lessons Learned from a European Adult Education Project - Alonso de Castro, María Goretti; Ruiz de la Peña, Telma (Avances en Supervisión Educativa, 2026)
This article provides an in-depth analysis of the design, development, and implementation of an Erasmus+ KA122-ADU project led by the Educational Inspectorate of the Community of Madrid. It outlines the formation of the initial team, the main institutional barriers encountered, and the solutions adopted to overcome them, as well as the selection of adult education as the project’s strategic focus. The paper also details the development of common tools for the systematic collection of evidence and presents a comparative analysis of the mobilities carried out in Belgium, Finland, France, Italy, Greece, Portugal and Sweden. Building on this process, the article reflects on the key lessons learned and their contribution to improving educational supervision. Overall, the project strengthens the strategic role of the inspectorate, enhances the European dimension of learning, and consolidates a collaborative working model with potential for future international initiatives.